Factors influencing self-management of adrenal crisis in patients with adrenal insufficiency: a qualitative study - Aldons Chua; Heather Yoeli; David Till; Umesh Dashora; Patrick Oyibo; William M Drake; Martin Cartwright; Sofia Llahana (Endocrine Connections)
Objective: Adrenal crisis is a life-threatening complication that requires urgent administration of parenteral hydrocortisone. Current patient education interventions remain ineffective, contributing to preventable hospitalisations and deaths. This study explored the lived experiences of individuals with adrenal insufficiency, focussing on the factors influencing self-management during adrenal crises. Methods: This qualitative study employed online semi-structured interviews with adults with adrenal insufficiency who had experienced at least one adrenal crisis in the past 3 years. Participants were recruited via patient advocacy groups in the United Kingdom. Data were analysed using an inductive thematic approach, allowing themes to emerge directly from the data without imposing predetermined categories. Results: Twelve themes, grouped into four overarching domains, captured individual experiences of managing adrenal crises: i) knowledge and experience; ii) tools and training; iii) psychological and emotional impact; and iv) support and dependence on others. Participants reported challenges including delayed diagnosis, difficulties recognising adrenal crisis symptoms and the complexity of the hydrocortisone injection process. However, prior experiences of adrenal crises, patient education and advocacy resources fostered greater confidence in self-management. Participants highlighted the need for simplified injection devices, clearer stress dosing guidelines, improved training for healthcare professionals and increased public awareness. Conclusion: Findings from this qualitative study emphasise that effective adrenal crisis management requires patient-centred, evidence-based interventions focussing on education, healthcare professional training and public awareness. Simplified hydrocortisone delivery devices and systemic reforms are crucial to supporting self-management and minimising preventable hospitalisations and fatalities caused by adrenal crises.